ISLAMOPHOBIA AND EMPIRICAL REVISIONISM: A CRITIQUE OF BUKAY AND BOSTOM - Abdelsalam, Elfatih A.; Katsina, Aliyu Mukhtar (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
The end of the Cold War saw the Western media, the Christian right, and the pseudo-intellectuals working stridently to project a specific image of Islam – both repulsive and retrogressive in nature – in the consciousness of the West. This leads to a form of Islamophobia in which pseudo-intellectuals write about Islam, aiming to obscure its positive attributes, amplify its supposedly repressive values, and capitalize on those areas of civilizational incompatibility and conflict with the Judeo-Christian West. An objective analysis of this hype provides two interesting revelations. One, a deliberate attempt to rubbish Islam through exaggerated lies and distortion of historical reality. Two, create and perpetuate fear about Islam in the consciousness of the West which ultimately breeds the desire for exterminating Muslims due to the existential threat which they pose to the West. In this review, we critique the assertions embedded in this type of discourse using the books of David Bukay and Andrew Bostom. We also discuss the specific Islamophobic frame through which most of these writings that fall short of intellectual rigor. In the final analysis, we show that, owing to this failure to adhere to the basic principles of scientific research, these writings are intended to misinform rather than enrich the current discourse on Islam.